The Northernmost Record of Champsodon nudivittis (Ogilby, 1895) in the Mediterranean Sea - Cem Dalyan; Onur Gönülal; Nur Bikem Kesici; Sercan Yapıcı (Aquatic Sciences and Engineering)
Champsodon nudivittis (Ogilby, 1895), also known as the nakedband gaper, is distributed in the Aegean and Levantine parts of the Mediterranean Sea. It has been reported in the Mediterranean Sea as a Red Sea immigrant. The first record of the species in the Mediterranean Sea was reported in 2009 from the Levantine coasts. In this study, two individuals of nakedband gaper were captured about two months apart from the north of Gokceada Island, in the North Aegean Sea. The specimens were obtained using a trawl at depths of 100-120 m. Their total lengths were measured as 117 and 122 mm. This report extends the distribution of C. nudivittis to the North Aegean Sea, marking its northernmost record in the Mediterranean Sea to date. Moreover, the species is the second Red Sea originated fish recorded in the area between Gokceada Island, Samothraki Island and Saros Bay. C. nudivittis is known as a predator, hence, its population density should be monitored and its impact on the ecosystem should be assessed in the North Aegean Sea.